Takhrij and Syarah Hadith of Agrotechnology: Utilization of Dead Land in Agriculture - Laylly Tria Sabila; Wahyudin Darmalaksana; Salamet Ginandjar (Gunung Djati Conference Series, 2021)
This study aims to discuss the hadith regarding the use of dead land in agriculture. This research method is a qualitative type through literature and field studies with the takhrij and syarah hadith approaches. The result and discussion of this research is that the management of dead land which in Islam is called ihyaul mawat is regulated in the provisions of the state in Indonesia where the land cannot be owned by individuals. The conclusion of this study is that there is a continuity between ihyaul mawat and the Islamic view of agrarian law in Indonesia in the use of dead land in the world of agriculture based on takhrij and syarah hadith agrotechnology.